Development and Evaluation of a Visual Novel Game “Happiness” to Introduce the 5 Stages of Grief - Lumombo, Liony; Pertiwi, Annisa (Universitas Pendidikan Indonesia (UPI), 2024)
Grieving is a feeling intimately associated with sadness and loss, and as a fundamental aspect of the human experience, it is an inevitable component of life. In the context of bereavement, individuals typically traverse the five stages of grief before achieving a state of equilibrium. However, the societal under-appreciation of these stages often engenders a prolonged and unresolved grief response, underscoring the necessity for educational initiatives that promote awareness of these stages. Visual game novels, a medium that employs narrative and visual elements to illustrate the stages of grief, offer a valuable avenue for conveying these concepts. These novels utilize Ren'py, a software application designed for creating visual novels, to present image illustrations alongside a narrative. In addressing this gap in understanding, the researcher developed a visual game novel titled